Laboratory diagnosis of Neisseria gonorrhoeae in St Petersburg, Russia: inventory, performance characteristics and recommended optimisations - Unemo, M; Savicheva, A; Budilovskaya, O; Sokolovsky, E; Larsson, M; Domeika, M (Sexually transmitted infections, 2006)
Objectives: To perform a comprehensive inventory of the number of samples, performance characteristics, and quality assurance of the laboratory diagnosis of Neisseria gonorrhoeae at five laboratories in St Petersburg and Leningradskaya Oblast, Russia, in 2004, and to recommend optimisations for an increased adherence to international evidence based recommendations of diagnostics. Methods: Surveillance data were obtained with questionnaire and site visits. For evaluation of the culture media utilised at the laboratories, N gonorrhoeae reference strains (n = 29) were used. Results: During 2004 the total numbers of N gonorrhoeae samples analysed at the five laboratories using microscopy of stained smears and culturing were 330 879 (407 positive) and 38 020 (420 positive), respectively. Four laboratories used a Russian non-selective culture medium—that is, Complegon, and one laboratory utilised Biocult-GC. Both media seemed suboptimal. Only two of the laboratories used any species confirmative assay. Antibiotic susceptibility testing of N gonorrhoeae was performed at only two of the laboratories and each year only occasional isolates were analysed. None of the laboratories comprised a complete laboratory quality assurance system. Conclusions: According to international recommendations, the diagnosis of N gonorrhoeae in St Petersburg and Leningradskaya Oblast, Russia, is suboptimal. More samples need to be analysed by culturing on a highly nutritious and selective medium and, furthermore, species confirmation and antibiotic susceptibility testing should be more frequently performed. In addition, the utilised methods for culturing and antibiotic susceptibility testing, including medium and interpretative criteria used, ought to be optimised, standardised, and quality assured using systematic internal and external quality controls.